Genotyping Fasciola hepatica by its1 and rapds suggests distinctive south american genetic diversity and host affinity - Scarcella, Silvana Andrea (2019)
The commonliver fluke Fasciola hepatica is a major cause of economic losses to agriculture all over the world, with cost estimatedat US$ 2000 million per annum, Given that the existence of genetically different populations of F. hepatica could allow, against any selection pressure, natural or artificial (for use fasciolicides products and/or control measures), one or more populations of F. hepatica to beable to survive and create resistance or adaptability to such selective pressure. It is important to characterize the different isolation of the liver fluke. The aim of the present work was to characterize genetically adult F. hepatica isolates from cattle, pigs, buffaloes and donkeys from different regions ofSouth American, using sequence analysis of ribosomal ITS1 and RAPD-PCR. Genotyping of Fasciola hepatica DNA samplesderived from, cattle, pig, buffalo, and donkey collected from different regionsof South America, were performed using the F.hepatica Internal Transcribed Spacer (ITS) sequencing, as well as RAPDs-PCR. Phylogeny assessment derived from multiple sequence alignment (MSA)of ITS sequences, exhibit a distinctive South American geographical pattern compared against F. hepatica reported ITS sequences from around the world, MSA analysis of ITS sequences also showed the F.hepatica ITS haplotypes found in south America are consistent with other reported ITS haplotypes. Further phylogenetic assessment of the electrophoresis band pattern of RAPDs-PCR amplicons, suggest the parasites genome contains markers that may reveal a host preference. Further assessment revealed twomajor F. hepatica groups within the South American isolates that clearly diverged from each other, one containing parasites obtained from swine and donkeys and other found in bovid with two additional branch subdivisions of the latter group one containing water-buffalos and a second containing only cattle.